ON THE ISSUE OF NATIONAL PECULIARITIES OF MODERNIZATION OF THE RUSSIAN POLITICAL ELITE IN THE XVII CENTURY - D. A. Filimonov (Вестник университета)
The beginning of the 18th century, the era of the transformations of Peter I, which affected many spheres of the life of Russian society, and, in particular, the restructuring of the upper political elite, were predetermined by the dynamics of the socio-economic and political processes of the XVII century. In other words, in the past changes it is necessary to highlight the objective component, separating it from the subjective characteristics of political figures of a particular historical era and, in particular, the personality of Emperor Peter I. An analysis of the peculiarities of the development of the highest political elite in the XVII century, in the era preceding the Peter the Great’s reforms has been given in the article. It is necessary to be aware of what its portrait was like at the beginning of the transformations, what processes formed it in this way. This allows you to evaluate what are the objective prerequisites for the reformatory actions of Peter I, and what kind of systemic resistance they objectively had to face.